HUBUNGAN BEBAN KERJA DAN MASA KERJA DENGAN KELUHAN NYERI LEHER PADA PENJAHIT DI LEMBAGA LATIHAN KERJA LUBUK PAKAM TAHUN 2020 - Delita Br Panjaitan; Raisha Octavariny; Sri Melda Br Bangun; Anggi Isnani Parinduri; Ade Julfiani Ritonga (JURNAL KESMAS DAN GIZI (JKG), 2021)
Complaints of neck pain are a complaint on the part of the skeletal muscle as a result of forced movement and receiving heavy loads for a long time. Tailoring is one of the jobs that has a high risk of experiencing neck pain complaints. The rotation of the spine when the body is bending is a factor in neck pain complaints that are often complained of by tailors. This work activity will indirectly endanger health. This study aims to determine the relationship between workload and work period with complaints of neck pain in tailors at the Lubuk Pakam Training Institute in 2020. The type of research used is quantitative with a cross sectional design. The population of this study were 30 workers at the Lubuk Pakam training institute using the total sampling technique. Data collection by questionnaire. Data analysis used the chi-square test at the level of confidence level of 95% and Î± = 0.05. The results showed that there was a significant relationship between workload (p = 0.024) and length of service (p-0.016) with complaints of neck pain in tailors at the Lubuk Pakam Training Institute. It is advisable for tailors to pay more attention to health and safety while working without forcing the body to work and regulating good working hours, adequate rest, stretching while working and paying attention to the dangers that can occur in the work environment